Sentiment Analysis of Bali Hai Cruises Reviews Using Support Vector Machine Algorithm - Akhmad, Ekka Pujo Ariesanto; Purwiyanto, Didik (Universitas Hang Tuah, 2024)
This paper presents sentiment analysis in online reviews using Support Vector Machine (SVM) algorithm. This research aims to classify the sentiment of online reviews into positive or negative by utilizing the SVM algorithm. The dataset used in this research consists of online reviews from May 2020 to April 2024 from www.tripadvisor.com. The results show the effectiveness of the SVM algorithm in accurately categorizing sentiment in online reviews, with a high level of precision and recall. The findings of this study have important implications for understanding and analyzing sentiment in online content, and can be utilized in various applications such as market research, customer feedback analysis, and opinion gathering.